2018
DOI: 10.1002/adsu.201800097
|View full text |Cite
|
Sign up to set email alerts
|

Silk Fibroin/Orange Peel Foam: An Efficient Biocomposite for Water Remediation

Abstract: A novel approach for the valorization of orange peel waste for the removal of aqueous organic pollutants is presented herein. The orange peel is combined with silk fibroin in order to obtain alcogels, which are successfully converted into highly porous biocomposite foams upon supercritical CO2 drying. The biocomposite shows a Brunauer–Emmett–Teller specific surface area of 174.45 m2 g−1 and can absorb three times its weight in water. The resulting adsorbents can adsorb methylene blue from water with a maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 56 publications
(84 reference statements)
0
12
0
Order By: Relevance
“…Complementary information obtained by combining nitrogen physisorption and MIP measurements on the two types of foams is essential for the quantification of the specific surface area and the more precise pore size distribution study in each case. , With the MIP technique, the macropore structures can be analyzed (under 110 μm), while this method is not suitable for the characterization of pore sizes below 0.01 μm. Therefore, for smaller pores, the nitrogen physisorption technique is adopted in order to investigate the structural characteristics of the pores in the microscopic (<2 nm) and mesoscopic (2–50 nm) ranges .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Complementary information obtained by combining nitrogen physisorption and MIP measurements on the two types of foams is essential for the quantification of the specific surface area and the more precise pore size distribution study in each case. , With the MIP technique, the macropore structures can be analyzed (under 110 μm), while this method is not suitable for the characterization of pore sizes below 0.01 μm. Therefore, for smaller pores, the nitrogen physisorption technique is adopted in order to investigate the structural characteristics of the pores in the microscopic (<2 nm) and mesoscopic (2–50 nm) ranges .…”
Section: Results and Discussionmentioning
confidence: 99%
“…42 Many techniques have been followed to fabricate such hybrid materials into device form such as vacuum filtration, 43 layer-by-layer deposition, 44 drop casting, 45 and spin coating. 46 Each of these materials can be made into foam, 47 powder-based membranes 48 or bead form 33 with specific characteristics as a result of their mutually beneficial properties as mentioned earlier among the nanomaterials and synthetic membranes. The inimitable properties and efficiency of these hybrid materials will be discussed in the following sections.…”
Section: Functional Nanomaterials and Composite-based Devicesmentioning
confidence: 99%
“…[ 1,3 ] Especially when a highly porous structure is required, the complexity of the conventional foaming and electrospinning techniques and the large number of parameters that influence them makes the scale‐up process particularly difficult. [ 5 ] As a valuable alternative to those techniques, the simple evaporation of a polymer solution in a suitable solvent that can result in self‐assembled porous structures has been recently reported. [ 6,7 ] Specifically, it was observed that solvent−polymer interaction, polymer concentration, and evaporation rate are key factors to control dimension and morphology of the pores.…”
Section: Figurementioning
confidence: 99%